What's new in equine recurrent uveitis?. Issue 6 (9th July 2020) - Malalana, Fernando
Abstract : Background: Equine recurrent uveitis is a spontaneous disease characterised by repeated episodes of intraocular inflammation and pain. Uveitis can have very serious impacts on vision and it is the most common cause of blindness in horses. While an inciting cause is not always clear, microbial factors and genetic predisposition may play a significant role in a large number of cases. Aim of the article: This article provides an overview of recent advances in the knowledge of this disease.